Counting and construction of holomorphic primary fields in free CFT4 from rings of functions on Calabi-Yau orbifolds - de Mello Koch, Robert; Rabambi, Phumudzo; Rabe, Randle; Ramgoolam, Sanjaye (The journal of high energy physics, 2017)
A bstract Counting formulae for general primary fields in free four dimensional conformal field theories of scalars, vectors and matrices are derived. These are specialised to count primaries which obey extremality conditions defined in terms of the dimensions and left or right spins (i.e. in terms of relations between the charges under the Cartan subgroup of SO(4, 2)). The construction of primary fields for scalar field theory is mapped to a problem of determining multi-variable polynomials subject to a system of symmetry and differential constraints. For the extremal primaries, we give a construction in terms of holomorphic polynomial functions on permutation orbifolds, which are shown to be Calabi-Yau spaces.